Course setting and selected biomechanical variables related to injury risk in alpine ski racing: an explorative case study - Spörri, J.; Kröll, J.; Schwameder, H.; Schiefermüller, C.; Müller, E. (British Journal of Sports Medicine, 2012)
Background: Course setting has often been discussed as a potential preventative measure in the World Cup ski-racing community. However, there is limited understanding of how it is related to injury risk. Objective: This study was undertaken to investigate the effect of increased horizontal gate distance on energy-related and injury mechanism-related variables. Methods: During a video-based three-dimensional (3D)-kinematic field measurement, a top world-class racer performed giant slalom runs at two course settings with different horizontal gate distances. A full-body segment model was reconstructed in 3D and selected biomechanical parameters were calculated. Results: For the analysed turn, no significant differences were found in turn speed for increased horizontal gate distance. However, a large effect size was observed for speed reduction towards the end of the turn. Turn forces were by tendency higher at the beginning and significantly higher towards the end of the turn. Additionally, significant differences were found in higher inward leaning, and large effect sizes were observed for a decreased fore/aft position after gate passage. Conclusions: On the basis of the data of this study, no final conclusion can be made about whether, for a section of consecutive turns, increasing horizontal gate distance is an effective tool for speed reduction. However, this study pointed out two major drawbacks of this course setting modification: (1) it may increase fatigue as a consequence of loading forces acting over a longer duration; (2) it may increase the risk of out-of-balance situations by forcing the athlete to exhaust his backward and inward leaning spectrum.